Wykonywanie diagnostyki i podejmowanie decyzji diagnostycznej w świetle przepisów prawa - Walter de Walthoffen, Szymon Jerzy (Studia Prawa Publicznego, 2025)
The purpose of diagnostic testing is to facilitate rapid and effective diagnostic decision-making, which constitutes a key element of medical practice. Under current legal regulations, a diagnosis cannot be established without conducting appropriate diagnostic tests, indicating their indispensability and confirming the causal relationship between these processes. Diagnostics is based on the analysis of clinical data, including findings from additional examinations such as medical (objective and subjective), laboratory, and pathomorphological ones, as well as imaging and non-imaging diagnostics. Legal provisions define the entities authorized to collect biological materials and conduct tests, thereby shaping the scope of competencies of various medical professions. This article systematizes the diagnostic terminology and evaluates its classification as a health service under the applicable legal framework. The analysis includes an interpretation of the terms diagnostic test, diagnosis, pathomorphological diagnosis, and diagnostic decision, along with their legal implications. Additionally, the study classifies professional entitlements related to diagnostic testing and assesses their qualification as health services in accordance with existing regulations. The article also highlights ambiguities and normative gaps that may lead to interpretative challenges in medical practice, particularly in delineating the competencies of various professional groups and defining their liability for diagnostic decisions. The findings emphasize the need for legislative revisions to ensure regulatory coherence and explicitly classify diagnostics as a health service. The study employs the dogmatic-legal method, based on analyzing and interpreting normative acts, allowing for the legal status of diagnostic testing within the healthcare system to be determined precisely. Consideration should also be given to introducing more precise regulations governing diagnostic procedures to eliminate interpretative uncertainties.